(3UhQI GdCQVs - (3GHf Mhbd , eMeO Hf Mhbd GdfUjHj GdHZOGOj GdehUdj, CHh GdbGSe,J (B367 (3g` s ((3Ydi Hf GdMSf Hf HfOGQ s)
(3ChdgG (B:s
(3CeG HYO aEf CMb ef QbG Edi GdecGQe aMd efgG ai GdPQhI s
(3BNQgG (B:s
(3hLeYjg dGJHdZ eSGaJg CQHY eGjI ef MdH Ydi GdMbjbI s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B111 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B5s
Keywords: (3GdLZQGajG h GdHdOGfs